The Kinetic Equations of Addition Processes by the Free-Radical Nonbranched-Chain Mechanism (International Journal of Innovative Research in Computer Science & Technology, 2017)
The aim of this study was the conclusion of simple  kinetic equations to describe ab initio initiated nonbranched chain processes of the saturated free-radical addition to the  double bonds of unsaturated molecules in the binary reaction  systems of saturated and unsaturated components. In the  processes of this kind the formation rate of the molecular  addition products (1:1 adducts) as a function of concentration of  the unsaturated component has a maximum. Five reaction  schemes are suggested for this addition processes. The proposed  schemes include the reaction competing with chain propagation  reactions through a reactive free radical. The chain evolution  stage in these schemes involves three or four types of free  radicals. One of them is relatively low-reactive and inhibits the  chain process by shortening of the kinetic chain length. Based on  the suggested schemes, nine rate equations (containing one to  three parameters to be determined directly) are deduced using  quasi-steady-state treatment. These equations provide good fits  for the nonmonotonic (peaking) dependences of the formation  rates of the molecular products (1:1 adducts) on the  concentration of the unsaturated component in binary systems  consisting of a saturated component (hydrocarbon, alcohol, etc.)  and an unsaturated component (alkene, allyl alcohol,  formaldehyde, or dioxygen). The unsaturated compound in these  systems is both a reactant and an autoinhibitor generating low reactive free radicals. A similar kinetic description is applicable  to the nonbranched-chain process of the free-radical hydrogen  oxidation, in which the oxygen with the increase of its  concentration begins to act as an oxidation autoingibitor (or an  antioxidant). The energetics of the key radical-molecule  reactions is considered.
Keywords: binary system; unsaturated compound; low reactive radical; autoinhibitor; competing reaction; parameters; hermochemical data; energy